2001
DOI: 10.1159/000063226
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Febrile Neutropenia with Cefepime Monotherapy

Abstract: Background and Objective: The empirical administration of a broad-spectrum β-lactam antibiotic, either as monotherapy or in combination with an aminoglycoside, is an essential component of the initial management of patients with fever and severe neutropenia. Multiple antibiotics have been tested for this indication. Cefepime is a fourth-generation cephalosporin with in vitro activity against most gram-negative and many gram-positive bacteria. We have studied the use of this agent as monotherapy in this indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
4
6
0
Order By: Relevance
“…Severe studies have compared the effi cacy of cefepiem vs. ceftazidime in management of febrile episodes in neutropenia patients. The results of other previous studies [3][4][5][6][7][8] were comparable with our study that cefepime appears to be effi cacious as ceftazidime in the management of febrile episodes in neutropenic patients.…”
Section: Discussionsupporting
confidence: 92%
“…Severe studies have compared the effi cacy of cefepiem vs. ceftazidime in management of febrile episodes in neutropenia patients. The results of other previous studies [3][4][5][6][7][8] were comparable with our study that cefepime appears to be effi cacious as ceftazidime in the management of febrile episodes in neutropenic patients.…”
Section: Discussionsupporting
confidence: 92%
“…In our trial, the overall resolution of the febrile episode was observed in 92% of cases in both groups, similar to other studies [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…The population studied in our trial was similar to that of other studies with respect to the main disease (acute leukemia in approximately half of the cases) [4,18,20,22,27,30] and the rates of granulocytopenia (>90% of episodes had <500 cells/mm 3 ). The time to defervescence was very short (a median of 3 days in both groups) and the need for changing or adding other antimicrobials was surprisingly low (39 and 33% of episodes, respectively) compared to other trials, with approximately two-thirds of the episodes (49-70%) in which the antibiotic therapy had to be modified [4,18,22].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Cefepime is another fourth-generation cephalosporin antibiotic with a broader spectrum of activity against Gram-positive and Gram-negative bacteria. (JANDULA et al, 2001) It is widely applied in clinical trials against infection worldwide due to its superior pharmacological characteristics. Several reports have indicated the effectiveness of cefepime, both with monotherapy or combination therapy, on FN treatment.…”
Section: Introductionmentioning
confidence: 99%